The evolution of galaxy number density at z < 8 and its implications - Conselice, Christopher J.; Wilkinson, Aaron; Duncan, Kenneth; Mortlock, Alice (American Astronomical Society, 2016)
The evolution of the number density of galaxies in the universe, and thus also the total number of galaxies, is a fundamental question with implications for a host of astrophysical problems including galaxy evolution and cosmology. However there has never been a detailed study of this important measurement, nor a clear path to answer it. To address this we use observed galaxy stellar mass functions up to z _ 8 to determine how the number densities of galaxies changes as a function of time and mass limit. We show that the increase in the total number density of galaxies (_T), more massive than M∗ = 106 M⊙ , decreases as _T _ t−1, where t is the age of the universe. We further show that this evolution turns-over and rather increases with time at higher mass lower limits of M∗ > 107 M⊙ . By using the M∗ = 106 M⊙ lower limit we further show that the total number of galaxies in the universe up to z = 8 is 2.0+0.7 −0.6 × 1012 (two trillion), almost a factor of ten higher than would be seen in an all sky survey at Hubble Ultra-Deep Field depth. We discuss the implications for these results for galaxy evolution, as well as compare our results with the latest models of galaxy formation. These results also reveal that the cosmic background light in the optical and near-infrared likely arise from these unobserved faint galaxies. We also show how these results solve the question of why the sky at night is dark, otherwise known as Olbers’ paradox.